PERCEPTION OF WORK IN DIFFERENT RELIGIOUS SYSTEMS - Hayrapetyan, D. R. (Արդի հոգեբանություն, 2019)
The issue of employment for the human being has always been central to all periods of time and this has caused great attention in both scientific and religious systems. The work as a phenomena came into psychology in the 19th century due to the American psychologist F. Taylor, later G. Emerson paid attention on it and after that representatives of the American Social- Psychological School. In the above mentioned era, the efficiency of the workers was a primary issue, but along with the development of the field, the raised issues were also increased. Nowadays, one of the primary issues of organizational psychology are the choice of employee, work motivation and job management. While discussing the issue of choosing an employee in professional literature, a great attention is paid both on the employee’s professional abilities and personality traits. Nevertheless, different religious systems, even during the creation of their saint books, have clearly described how working relationships should be, who should be accept to the certain work, how to work, and how to pay the worker. So this article is directed to the research how different religious systems refer to work and how experts interpret it.